2011
DOI: 10.1007/s00431-011-1486-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical correlates of radiographic patterns of bronchopulmonary dysplasia in very low birth weight infants by term age

Abstract: Radiographic BPD findings appeared to be common in VLBW infants. In addition to the well-known respiratory risk factors (oxygen and ventilator therapy), poor nutrition and excessive fluid administration in early life seem to be significantly associated with radiological findings of lung injury in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…84 Nine studies defined CA using a microbiological definition. 28,29,47,53,58,64,131,135,152 Finally, 16 studies 102,104,105,108,113,120,123,128,129,130,139,141,148,155,160,170 did not define CA and, for the purposes of analysis, were considered to evaluate clinical CA.…”
Section: Resultsmentioning
confidence: 99%
“…84 Nine studies defined CA using a microbiological definition. 28,29,47,53,58,64,131,135,152 Finally, 16 studies 102,104,105,108,113,120,123,128,129,130,139,141,148,155,160,170 did not define CA and, for the purposes of analysis, were considered to evaluate clinical CA.…”
Section: Resultsmentioning
confidence: 99%
“…CR has demonstrated its capability to predict the evolution of BPD in preterm infants at high risk. Hyödynmaa et al 97 showed that most (89.5%) of the patients who would develop moderate‐to‐severe BPD at 36 weeks PMA had one of the two radiological patterns of leaky lung syndrome (LLS) with hazy/opaque lungs, or cystic BPD (cBPD) with bubbly lung changes. Oxygen demand at discharge is an independent risk factor for cBPD (odds ratio OR 3) 98 .…”
Section: Chest Radiographymentioning
confidence: 99%
“…In our study, we focused on the interstitial changes alone in evaluating chest radiographs. The interstitial changes on the day 7 chest radiographs were easily noticeable, and a high degree of agreement between observers was obtained [16]. Furthermore, interstitial changes on chest radiograph are less influenced by inflation status, which will be variable in the preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic changes on chest radiograph are also associated with BPD or death [11]. However, we did not evaluate cystic changes in this study because cystic changes on chest radiographs were more difficult to distinguish from other diseases, such as infection, sequelae of pulmonary hemorrhage, and pulmonary interstitial emphysema [16]. In addition, cystic changes on chest radiograph represent chronic pathological changes and appear later [17].…”
Section: Discussionmentioning
confidence: 99%